GAMBARAN TINGKAT PENGETAHUAN IBU HAMIL TRIMESTER III TENTANG RISIKO MASTITIS - Rissa Rahmawati Harahap; Agrina Agrina; Sri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Mastitis is one of the problems that mothers can experience during the breastfeeding process and this situation is the reason for mothers to stop giving exclusive breastfeeding to their babies, one of the influencing factors is the mother's level of knowledge. This study aims to determine the effect of using video media on increasing the knowledge of third trimester pregnant women about the risk of mastitis at the Harapan Raya Health Center. This study used a quasi-experimental design with a non-equivalent control group design with a total sample of 34 respondents using a sampling technique, namely purposive sampling. Data analysis used is bivariate analysis using dependent sample t-test and independent sample t-test. The results of the dependent t-test obtained in the experimental group, namely p value 0.000 < 0.005, showed that there was a significant effect on health education using video media on increasing knowledge of third trimester pregnant women about the risk of mastitis, in the control group, p value 0.431 > 0.005 was not found. the effect of increasing maternal knowledge on the risk of mastitis. It can be concluded that video media has an effect on increasing the knowledge of third trimester pregnant women about the risk of mastitis Keywords: media videos, knowledge, Mastitis risk